Tordylium persicum Boiss. & Hausskn extract: A possible alternative for treatment of pediatric infectious diseases - Sharifi-Rad, J; Fallah, F; Setzer, W N; Entezari Heravi, R; Sharifi-Rad, M (Cellular and Molecular Biology, 2016)
Antimicrobial herbal compounds are one of the important medical resources, and in order to help alleviate the spread of the pediatric infectious diseases, identification of additional bioactive phytochemicals and herbal extracts will be practical in treating illnesses. In the present work, antimicrobial activities various extracts of Tordylium persicum Boiss. & Hausskn aerial parts were determined against five Gram-positive bacteria, five Gram-negative bacteria, two fungi, and Echinococcus granulosus. Antimicrobial activities were assayed using both disk diffusion and microbroth dilution methods. Scolicidal activity was assayed by the Smyth and Barrett method. Also total phenol and total flavonoid contents for plant extracts were assayed. Results showed that the methanolic extract was more effective on all microbes. The results showed that Streptococcus pyogenes was the most susceptible to the methanolic extract (MIC = 25.9 ± 0.0 µg/mL), while Proteus vulgaris was the most resistant strain (MIC = 295.3 ± 0.0 µg/mL) among all bacteria evaluated. The extracts showed significant activity versus E. granulosus (P < 0.5) with dose-dependent inhibitions of the protoscolices. The high concentration of total polyphenolics (294.5 ± 0.1 GAE/g DW) and flavonoids (105.7 ± 0.3 mg CE/g DW) may be responsible for these activities. Our study is first evaluation on antimicrobial and scolicidal activities of T. persicum. Due to the appearance of antibiotic-resistance, ourstudy suggested that methanol extracts of this plant are appropriate candidate for traditional curative uses and it can be utilized in the pediatric infectious disease therapy, especially pediatric infectious disease.